Enhancing motivation in vocabulary learning via online games: An action research project at a university in Hanoi - Đặng, Minh Anh (2020)
The present thesis was conducted to examine the extent to which the application of Online games could help to enhance the students’ motivation in learning vocabulary. Participants of this study were 28 low-level students in a non-English major university in Hanoi. Online games was used as the strategy to enhance students’ motivation in vocabulary learning. This thesis was designed as an action research. The whole process of the research was divided into four steps of planning, implementing, observing and reflecting on progress with aims to reduce the problems and to improve students’ motivation in learning vocabulary. The research questions to be addressed in the thesis are: (1) To what extent do online games have influences on students’ motivation in learning vocabulary? (2) What are students’ opinions towards the application of these games in vocabulary learning. Survey questionnaire, semi-structured interview and classroom observation were used as instruments to collect data for reflection throughout the research. The results had confirmed the positive effects of online games on enhancing their motivation in vocabulary learning as the level of motivation after the intervention was increase significantly in comparison with that before the intervention. In addition, the results indicated that the students had positive opinions towards application of online games in vocabulary learning in all aspects of ARSC model.